Cardiovascular Practice and Services in Indonesia: Where are We Now and What should we Improve? - Andriany Qanitha; Idar Mappangara; Nurul Qalby; Muzakkir Amir (Research Developments in Medicine and Medical Science Vol. 5, 2023)
Despite advancements in cardiovascular services over the past years, low- and middle-income countries (LMICs) in the South-East Asia region—particularly Indonesia—continue to face a variety of difficulties in delivering standardized services and healthcare systems. This chapter aims to highlight the present status of cardiology practices in primary and secondary care, including the novel cardiovascular risk factors, suggestions for enhancing the quality of care, and future directions of cardiovascular research in poor-resource settings in South-East Asia. We also shed a light in the context of research in Indonesia, a country with limited infrastructure, human capability, and financial resources in conducting basic and clinical research. Exposure to CVD risk factors can be nationally reduced with better healthcare legislation and regulations; and reducing the cardiovascular mortality and morbidity in this country is possible by providing inexpensive and accessible cardiovascular detection and treatment, both at primary and secondary levels. Finally, improving the capacity building for clinical research should be warranted in this LMIC to better understand the needs, features, and current problems in cardiovascular healthcare.